DEVELOPMENT OF INTEGRATED EDUCATION MANAGEMENT INFORMATION SYSTEM AS THE DATABASE OF EDUCATION BUDGET POLICY FORMULATION - Dadan Rosana; Sukardiyono Sukardiyono (Journal of Science Education Research, 2017)
The objective of this research is to produce the integrated education management information system as database for  education budget policy formulation. The database that is precise, accurate, complete and taransparan is  accessible to the public via the web in the android system, is a key element in any policy formulation and budget proposals in the field of education, that it can  be used to reduce the corruption in the education area in a systematic which began drafting the state budget and regional budget. this research is a development that adapt the model Borg and Gall (1983). aiken's formula v is used to analyze the instrument by the validator. The concept is to package products and services in one unit. To produce a product, a common cycle passed are: system specification, design, production, distribution, setup, use, maintenance, and renewal. The results of research is already made education management information system based on national education standards and geografic information system that has been tested is limited in some schools in the district region in indonesia. The policy recommendations of this research will support the government to modernize management of the education budgeting sector.